Does economic development mitigate tax evasion? evidence from evasional Kuznets curve - Tan, Yan Ling; Habibullah, Muzafar Shah; Din, Badariah; Kaliappan, Shivee Ranjanee (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
The purpose of this study is to estimate the size of the shadow economy in Malaysia for the period 1983 to 2013 using the currency demand approach (CDA). We employ the nonlinear autoregressive distributed lag (NARDL) modeling approach and calculate the loss in tax revenue (tax evasion) as a result of the presence of the shadow economy. We analyse factors determining tax evasion in Malaysia and our results suggest that tax evasion exhibit an inverted-U shape curve (nonlinear) with the level of economic development and positive relationship with various measures of tax burden in Malaysia during the period under study. We conclude that increasing the level of economic development and reducing the various tax rates will able to reduce tax evasion in Malaysia.